Lithium secondary battery structure including composite conductive current collector
By adopting a combined structure of metal current collector and composite conductive current collector in lithium secondary batteries, the problems of ignition risk and output characteristics of lithium secondary batteries in short circuit situations are solved, and excellent safety and output characteristics are achieved.
Patent Information
- Application Number
- CN202380058363.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-04
- Filing Date
- 2023-10-30
- Publication Date
- 2025-03-18
AI Technical Summary
Lithium secondary batteries are prone to ignition in the case of short circuit, and the increase in resistance of traditional aluminum positive current collectors leads to deterioration of output characteristics.
The combined structure of metal current collector and composite conductive current collector is adopted, and the stability and output characteristics of the battery are improved by adjusting their ratio and alternate arrangement.
Improved output characteristics and life characteristics based on excellent safety, reduce the risk of ignition and explosion, and maintain high energy density and stable electrochemical performance.
Smart Images

Figure CN119654731A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a lithium secondary battery structure that suppresses heat generation or ignition, thereby exhibiting improved output characteristics while having excellent safety. Background Art
[0002] Recently, with the increase in technological development and demand for mobile devices, the demand for rechargeable / dischargeable secondary batteries as energy sources has rapidly increased, and therefore various studies have been conducted on secondary batteries that can meet various needs. In addition, secondary batteries have attracted considerable attention as a power source for electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (Plug-in HEVs), etc., which are developed to solve problems such as air pollution caused by existing gasoline and diesel vehicles using fossil fuels.
[0003] Therefore, electric vehicles (EVs) that can be driven using only secondary batteries and hybrid electric vehicles (HEVs) that use a secondary battery and a conventional engine in combination have been developed, some of which are already in commercial use. Nickel metal hydride (Ni-MH) secondary batteries are mainly used as a power source for EVs, HEVs, etc. However, in recent years, active research has been conducted on the use of lithium secondary batteries with high energy density, high discharge voltage, and output stability, some of which are already in commercial use.
[0004] Such a lithium secondary battery is manufactured by applying an electrode slurry containing an electrode active material to an electrode collector, drying and rolling to produce an electrode, and then embedding an electrode assembly (in which a separator is interposed between the electrodes) in a battery case together with an electrolyte solution.
[0005] Meanwhile, copper or aluminum is generally used as a material for an electrode current collector, however, aluminum used as a conventional positive electrode current collector has a problem in that it exhibits a dangerous mode of contacting with a negative electrode active material in the event of a short circuit, thereby causing fire.
[0006] In order to solve this problem, attempts have been made to replace the conventional aluminum positive electrode collector with a collector coated with aluminum on a PET substrate. However, in this case, the resistance of the collector itself increases, and even when it is in contact with the negative electrode active material, the short-circuit resistance increases, which is expected to reduce the possibility of fire during safety verification, while the resistance of the entire battery increases, which causes the problem of deterioration of output characteristics.
[0007] Therefore, there continues to be a need to develop a technology for applying organic / metal composite materials as metal current collectors, thereby enabling improved output characteristics, etc. while achieving high stability. Summary of the invention
[0008] Technical issues
[0009] An object of the present disclosure is to provide a lithium secondary battery structure that suppresses heat generation or ignition due to external impact or the like, thereby exhibiting improved output characteristics while having excellent safety.
[0010] Another object of the present disclosure is to provide a lithium secondary battery structure including a metal current collector and a composite conductive current collector, thereby exhibiting excellent stability and improved lifespan characteristics.
[0011] Technical Solution
[0012] Hereinafter, a lithium secondary battery structure and the like according to a specific embodiment of the present disclosure will be described.
[0013] The terms or words used in the specification and the appended claims should not be construed as being limited to the ordinary or dictionary meanings, and the present disclosure should be interpreted with meanings and concepts consistent with the technical ideas of the present disclosure based on the principle that inventors can appropriately define the concepts of the terms to appropriately describe their own inventions in the best manner.
[0014] The terms used herein are used to describe exemplary embodiments but do not limit the inventive concept. Unless the context clearly indicates otherwise, the singular includes the plural.
[0015] It should be understood that the terms "including", "comprising", "having" and the like are used herein to specify the presence of stated features, numbers, steps, components or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, components or a combination thereof.
[0016] According to one embodiment of the present disclosure, a lithium secondary battery structure is provided, including a plurality of battery cells A and B, each battery cell including: a first electrode 100 including a first conductive collector 110 having an active material layer 120 formed on at least one surface; a second electrode 200 including a second conductive collector 210 having an active material layer 220 formed on at least one surface; and a separator 300 formed between the active material layers 120 and 220 of the first electrode and the second electrode facing each other, wherein for each battery cell, the first conductive collector 110 or the second conductive collector 210 is a metal collector, or a composite conductive collector 110' having a metal layer 112 formed on a polymer substrate 111, and wherein the metal collector: the composite conductive collector is included in the total battery structure in a quantitative ratio of 5:1 to 1:5.
[0017] The present inventors have continued research and experiments to develop a secondary battery that achieves high stability while having improved output characteristics, etc., unlike conventional secondary batteries that apply a composite current collector coated with aluminum on an aluminum foil positive electrode current collector or a polymer such as PET.
[0018] From the results of these ongoing studies, it was found that when a metal current collector and a composite conductive current collector coated with a metal layer on a polymer are combined as the current collector of each battery cell in a battery structure including a plurality of battery cells, excellent performance can be obtained. In particular, it has been found that by adjusting the ratio of the metal current collector to the composite conductive current collector used in the entire battery structure, stability and battery performance can be improved at the same time.
[0019] Aluminum used as a conventional positive electrode collector has low resistance characteristics, but when a short circuit occurs, it comes into contact with the negative electrode active material and causes ignition, which results in low stability. In the case of a composite conductive collector in which a metal layer is coated on a polymer, the resistance of the collector itself becomes larger, and even if it comes into contact with the negative electrode active material, the short circuit resistance becomes larger, so it has excellent stability, but the resistance of the entire battery increases, and the output characteristics deteriorate, so that there is a trade-off relationship between stability characteristics and output characteristics. Therefore, by adjusting the ratio of the metal collector and the composite conductive collector, or by regularly and alternately arranging the metal collector and the composite conductive collector, a good level of stability and output characteristics can be obtained.
[0020] Such excellent output characteristics can be supported by the measurement results of the initial resistance of the test examples described below, the excellent stability can be supported by the low ignition rate and explosion rate in the impact test of the test examples described below, and the life characteristics can be confirmed by, for example, the excellent capacity retention rate of 80% or more or 90% or more after 300 cycles from the evaluation results of the life characteristics according to the charge and discharge procedure at room temperature in the embodiments described below.
[0021] Meanwhile, in one embodiment of the present disclosure, the metal current collector supports the active material layers 120 and 220, and is not particularly limited as long as they have conductivity without causing chemical changes in the corresponding battery. For example, the metal current collector may be made of copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc.
[0022] Further, the metal current collectors 110 and 210 may form fine protrusions and depressions on their surfaces, and may enhance the bonding strength with the active material layer. Therefore, the metal current collector may be used in any of various forms including films, sheets, foils, meshes, nets, porous bodies, foams, and non-woven fabric structures. For example, the metal current collector may be aluminum foil.
[0023] In one embodiment, composite conductive current collector 110' may have a structure in which metal layer 112 is formed on polymer substrate 111. Specifically, composite conductive current collector 110' has a three-layer laminated structure in which metal layers 112 may be formed on both surfaces of polymer substrate 111, respectively.
[0024] In the case of a positive electrode current collector made of a metal material, flexibility is not excellent due to the metal and it is difficult to achieve lightweight performance of the battery, but due to the polymer substrate 111, the flexibility and lightweight performance of the battery can be ensured, and the metal layer 112 can also be used to impart the same conductivity as that of a current collector made of a single metal material, thereby preventing a decrease in battery performance.
[0025] In one embodiment, the polymer substrate 111 may be a polyester-based resin substrate. For example, the polyester-based resin may include a resin such as polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), polybutylene terephthalate (PBT), or polyethylene naphthalate (PEN). Preferably, the polymer substrate may be a polyethylene terephthalate (PET) substrate.
[0026] Further, in one embodiment, the metal layer 112 may be a metal layer such as stainless steel, aluminum, copper, nickel or titanium, or copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. Further, the metal layer may form fine protrusions and depressions on its surface, and may be used in any of various forms including films, sheets, foils, meshes, nets, porous bodies, foams, and non-woven fabric structures. For example, the metal layer may be an aluminum layer.
[0027] At the same time, by adjusting the thickness ratio of the polymer substrate 111 and the metal layer 112 included in the composite conductive current collector 110', the processability and electrochemical performance and stability of the battery can be improved. For example, in the composite conductive current collector 110', the ratio of the total thickness of the polymer substrate: the total thickness of the metal layer can be 1:2 to 5:1. However, if the thickness ratio of the polymer substrate is too high, the resistance may increase and the battery performance may deteriorate, and if the thickness ratio of the metal layer is high, a structure similar to a metal foil may result, and there may be no difference in stability.
[0028] In the lithium secondary battery structure according to one embodiment, for each battery cell, the first conductive current collector 110 or the second conductive current collector 210 may be a metal current collector, or a composite conductive current collector 110' in which a metal layer 112 is formed on a polymer substrate 111. At this time, the first conductive current collector 110 or the second conductive current collector 210 in at least one battery cell may be a composite conductive current collector 110'.
[0029] In one embodiment, the first electrode 100 is a positive electrode, and for each battery cell, the first conductive collector 110 may be a metal collector, or a composite conductive collector 110'. At this time, the first conductive collector 110 may have a thickness ranging from 6um to 20um. If the thickness range is too large or too small, or if the thickness is less than 6um, the R2R coating process may not be performed, and if the thickness is greater than 20um, the energy density loss per unit battery volume may be large.
[0030] In one embodiment, for each battery cell A, B, the first conductive current collector 110 is a metal current collector or a composite conductive current collector 110 ′, and the metal current collector and the composite conductive current collector may be alternately and regularly arranged according to the stacking sequence of the first electrode 100 .
[0031] Specifically, the metal current collector and the composite conductive current collector 100 ′ may be configured such that: according to the stacking sequence of the first electrode 100 , one composite conductive current collector 110 ′ is repeatedly arranged for every 1 to 3 metal current collectors, or one metal current collector is repeatedly arranged for every 1 to 3 composite conductive current collectors 110 ′.
[0032] For example, if a battery cell including a positive electrode to which a metal current collector is applied is denoted as A, and a battery cell including a positive electrode to which a composite conductive current collector is applied is denoted as B, they can be repeatedly arranged in the order of ABAB...ABAB, ABBABB...ABBABB, ABBBABBB...ABBBABBB, AABAAB...AABAAB, or AAAB...AAAB according to the stacking order of each battery cell. For reference, Figure 1 It is a schematic cross-sectional view of an embodiment of a lithium secondary battery structure, in which battery cell A including a positive electrode and a negative electrode using a metal current collector, battery cell B including a positive electrode using a composite conductive current collector and a negative electrode using a metal current collector, and battery cell A including a positive electrode and a negative electrode using a metal current collector are arranged alternately.
[0033] In one embodiment, when the metal current collector: composite conductive current collector is included in the entire battery structure at a ratio of 5:1 to 1:5, excellent output characteristics and life characteristics can be improved while ensuring a high level of stability. In particular, when the metal current collector and the composite conductive current collector are included at a ratio of 3:1 to 1:3, the best results can be expected. However, if the ratio is too large or too small, the stability characteristics or output characteristics may be deteriorated.
[0034] In an electrode of an embodiment, active material layers 120 and 220 are formed on both surfaces of the first conductive collector 110 and the second conductive collector 210, and the first electrode 100 and the second electrode 200 may be alternately stacked with the separator 300 interposed therebetween. For example, the active material layers 120 and 220 including an active material, a conductive material, and a binder may be formed on the first conductive collector 110 or the second conductive collector 210.
[0035] In such active material layers 120 and 220, if the active material is a positive electrode active material, the active material is not particularly limited as long as it is a material that can reversibly insert and extract lithium ions, and examples thereof include lithium metal composite oxides containing at least one metal element selected from the group consisting of Co, Mn, Ni, W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg and Mo.
[0036] More specifically, a compound represented by any one of the following formulae may be used as the positive electrode active material. a A 1-b R b D2 (where 0.90≤a≤1.8 and 0≤b≤0.5); Li a E 1-b R b O 2-c D c (where 0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); LiE 2-b R b O 4-c D c (where 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b R c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α≤2); Li a Ni 1-b-c Cob R c O 2-α Z α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Co b R c O 2-α Z2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Mn b R c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α≤2); Li a Ni 1-b-c Mn b R c O 2-α Z α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Mn b R c O 2-α Z2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni b E c G d O2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5 and 0.001≤d≤0.1); Li a Ni b Co c Mn d GeO2 (wherein 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5 and 0.001≤e≤0.1); Li a NeG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a CoG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a MnG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn bO4 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiTO2; LiNiVO4; and Li (3-f) J2(PO4)3(0≤f≤2).
[0037] In the above formula, A is Ni, Co, Mn or a combination thereof; R is Al, Ni, Co, Mn, Cr, Fe, Mg, V or a combination thereof; D is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; Z is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; T is Cr, V, Fe, Sc, Y or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu or a combination thereof.
[0038] Further, those having coating on the surface of the above compound can be used, or a mixture of the above compound and the compound having coating can be used. The coating can include an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, and a basic carbonate of a coating element as a coating element compound. The compound constituting these coatings can be an amorphous or crystalline compound. As the coating element included in the coating, Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr or a mixture thereof can be used.
[0039] In addition, the conductive material included in the positive electrode active material layer 120 is used to impart conductivity to the electrode, and the conductive material can be used without restriction as long as it has conductivity and does not cause chemical changes in the battery to be configured. Examples thereof include natural graphite, artificial graphite, carbon black, carbon fiber, carbon nanotubes, metal powders (such as copper, nickel, aluminum and silver), metal fibers, etc. Further, conductive materials such as polyphenylene derivatives can be used alone or in a mixture of one or more thereof. In addition, this conductive material can be the same as or different from the carbon-based conductive material contained in the above-mentioned safety protection layer.
[0040] The conductive material may be added in an amount of 1 wt % to 50 wt %, or 2 wt % to 20 wt %, based on the total weight of the positive active material layer 120. Thus, the positive electrode can be given excellent electrical characteristics while ensuring optimal formation of the positive electrode.
[0041] The binder plays a role in making the particles of the positive electrode active material adhere well to each other and further improving the binding performance of the positive electrode active material layer 120. As typical examples thereof, the above-mentioned halogenated polyolefin-based polymer binder, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymer, polyvinyl pyrrolidone, polyurethane, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, nylon, etc. can be used.
[0042] The binder may be added in an amount of 1 to 50 wt % or 2 to 30 wt % based on the total weight of the positive active material layer 120. Thus, a positive electrode having excellent durability may be formed without hindering the electrical characteristics and / or capacity characteristics of the positive electrode.
[0043] The positive active material layer 120 may be formed by dissolving or dispersing the positive active material, conductive material, and binder in a medium such as an organic solvent to form a slurry composition, and then coating the slurry composition on a conductive current collector and drying it.
[0044] At this time, examples of the medium such as an organic solvent include N-methyl-2-pyrrolidone (NMP), methoxypropyl acetate, butyl acetate, glycolic acid, butyl ester, butyl glycol, methyl alkyl polysiloxane, alkylbenzene, propylene glycol, xylene, monophenyl glycol, etc., and among them, NMP, etc. can be appropriately used.
[0045] However, since the formation process and conditions of the positive electrode active material layer 120 may follow general positive electrode formation processes and conditions, further description thereof will be omitted.
[0046] The positive active material layer 120 described above may be formed to a thickness of, for example, 10 to 300 μm or 15 to 200 μm, and as a result, may exhibit excellent safety and electrical characteristics during charge and discharge.
[0047] Meanwhile, according to another embodiment of the present disclosure, individual battery cells A and B including the positive electrode 100, the negative electrode 200, and the separator 300 interposed therebetween are provided, and a lithium secondary battery structure may be formed by including a plurality of such battery cells.
[0048] In a lithium secondary battery as a battery cell of other embodiments, the negative electrode 200 is manufactured by applying, drying, and rolling a negative electrode active material on a negative electrode collector 210 , and optionally, the negative electrode 200 may further include a conductive material and a binder.
[0049] The negative electrode active material may include, for example, graphite having a complete layered crystal structure, such as natural graphite, a low-crystalline layered crystal structure (graphene structure, graphene structure, in which hexagonal honeycomb carbon planes are arranged in the form of layers), soft carbon having a structure in which a low crystalline structure is mixed with an amorphous part, carbon and graphite materials, such as artificial graphite, expanded graphite, carbon fiber, carbon that is difficult to graphitize, carbon black, carbon nanotubes, fullerenes, activated carbon; or metal composite oxides, such as LixFe2O3 (0≤x≤1), LixWO2 (0≤x≤1), SnxMel-xMe'yOz (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Groups 1, 2, and 3 in the periodic table, halogen; 0<x≤1; 1≤y≤3; 1≤z≤8); lithium metal; lithium alloy; silicon, silicon oxide or silicon-based alloy; tin-based alloy; conductive polymers, such as polyacetylene; Li-Co-Ni-based materials; titanium oxide; or lithium titanium oxide, etc.
[0050] In one embodiment, the negative electrode active material may include both graphite and silicon (Si)-containing particles, the graphite may include at least one of natural graphite having a layered crystal structure and artificial graphite having an isotropic structure, and the silicon (Si)-containing particles include particles with silicon (Si) as a main component as a metal component, and the particles with silicon (Si) as a main component may include silicon (Si) particles, silicon oxide particles, or a mixture of silicon (Si) particles and silicon oxide particles.
[0051] In addition, the conductive material and the binder that may be used together with the negative electrode active material may be the same components as those contained in the positive electrode active material layer 120 .
[0052] Further, the negative electrode active material layer 220 containing the negative electrode active material may have an average thickness of 100 μm to 200 μm, specifically, it may have an average thickness of 100 μm to 180 μm, 100 μm to 150 μm, 120 μm to 200 μm, 140 μm to 200 μm, or 140 μm to 160 μm.
[0053] In addition, the negative electrode current collector 210 is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, nickel, titanium, sintered carbon, etc. can be used, and in the case of copper or stainless steel, a material surface-treated with carbon, nickel, titanium, silver, etc. can be used.
[0054] In addition, similar to the positive electrode collector 110, the negative electrode collector 210 may have fine protrusions and depressions formed on its surface to enhance the adhesion of the negative electrode active material layer 220, and may be formed in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabric structures. In addition, considering the conductivity and total thickness of the negative electrode to be produced, the average thickness of the negative electrode collector 210 may be appropriately applied within the range of 3 to 500 μm.
[0055] Further, the separator 300 is interposed between the positive electrode 100 and the negative electrode 200, and a thin insulating film with high ion permeability and mechanical strength is used. The separator 300 is not particularly limited as long as it is commonly used in this field. Specifically, chemically resistant and hydrophobic polypropylene; glass fiber; or a sheet or non-woven fabric made of polyethylene, etc. can be used. In some cases, a composite separator can be used in which inorganic particles / organic particles are coated on a porous polymer substrate such as a sheet or a non-woven fabric by an organic binder polymer. When a solid electrolyte such as a polymer is used as an electrolyte, the solid electrolyte can also act as a separator. In addition, the separator may have an average pore size of 0.01 to 10 μm and an average thickness of 5 to 300 μm.
[0056] The battery cell of the above-mentioned other embodiments may further include an electrolyte, wherein the electrolyte may be an electrolyte solution containing a non-aqueous organic solvent and a lithium salt, or an electrolyte membrane containing an organic or inorganic solid electrolyte, and these may be mixed and used together. However, the type of electrolyte that can be used is well known to those skilled in the art, and is not particularly limited in the batteries of other embodiments, and therefore further description thereof will be omitted.
[0057] Beneficial Effects
[0058] As described above, the lithium secondary battery structure of the present disclosure includes a certain ratio of a metal current collector and a composite conductive current collector within the entire battery structure, thereby improving output characteristics and the like while achieving excellent safety of the lithium secondary battery structure.
[0059] In addition, the lithium secondary battery structure can exhibit excellent lifespan characteristics at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 A cross-sectional view showing a structure of a lithium secondary battery according to one embodiment of the present disclosure is shown. DETAILED DESCRIPTION
[0061] Hereinafter, embodiments of the present disclosure will be described in detail so that those skilled in the art can easily implement them. However, the present disclosure can be modified in various different ways and is not limited to the embodiments set forth herein.
[0062] Comparative Example 1: Secondary battery structure using a metal current collector
[0063] First, the positive electrode active material (LCO): conductive material (carbon black): binder (PVdF) was mixed in an N-methylpyrrolidone (NMP) solvent at a mass ratio of 97:1.2:1.8 to prepare a positive electrode slurry. The slurry was then coated on a 10 um aluminum foil metal collector at a predetermined loading amount, dried, and then rolled to produce a double-sided positive electrode.
[0064] Then, as the negative electrode, the negative electrode active material (graphite): conductive material (carbon black): binder (SBR): CMC was mixed in a mass ratio of 95.35:0.5:3:1.15 to prepare a negative electrode slurry. The slurry was then applied to a current collector of 8um copper foil at a predetermined loading, dried, and then rolled to produce a negative electrode. A 10um thick separator coated with SRS on a polyolefin fabric was applied as a separator between the negative electrode and the positive electrode to produce a single cell (metal current collector).
[0065] The produced single cells were arranged into 24 cells to manufacture a lithium secondary battery structure.
[0066] Comparative Example 2: Secondary battery structure using a composite conductive current collector
[0067] First, the positive electrode active material (LCO): conductive material (carbon black): binder (PVdF) was mixed in an N-methylpyrrolidone (NMP) solvent at a mass ratio of 97:1.2:1.8 to prepare a positive electrode slurry. The slurry was then coated on a composite conductive current collector with a total thickness of 12um consisting of 1um aluminum / 10um PET / 1um aluminum at a predetermined loading amount, dried, and then rolled to produce a double-sided positive electrode.
[0068] Then, as the negative electrode, the negative electrode active material (graphite): conductive material (carbon black): binder (SBR): CMC was mixed in a mass ratio of 95.35:0.5:3:1.15 to prepare a negative electrode slurry. The slurry was then applied to a current collector of 8um copper foil at a predetermined loading, dried, and then rolled to produce a negative electrode. A 10um thick separator coated with SRS on a polyolefin fabric was applied as a separator between the negative electrode and the positive electrode to produce a single cell (composite conductive current collector).
[0069] The produced single cells were arranged into 24 cells to manufacture a lithium secondary battery structure.
[0070] Example 1: Secondary battery structure using a composite conductive current collector (metal: composite = 1:5)
[0071] A single cell produced in the same manner as in Comparative Example 1 (metal current collector, A) and a single cell produced in the same manner as in Comparative Example 2 (composite conductive current collector, B) were prepared.
[0072] Four cells A and 20 cells B are arranged in the order of ABBBBBABBBBB ... ABBBBBABBBBB to manufacture a lithium secondary battery structure. At this time, the ratio of the number of metal current collectors: composite conductive current collectors is set to 1:5.
[0073] Example 2: Secondary battery structure using a composite conductive current collector (metal: composite = 1:3)
[0074] The lithium secondary battery structure was manufactured in the same manner as in Example 1, except that the 6 cells A and 18 cells B produced in Example 1 were arranged in the order of ABBBABBB ... ABBBABBB. At this time, the ratio of the number of metal current collectors: composite conductive current collectors was set to 1:3.
[0075] Example 3: Secondary battery structure using a composite conductive current collector (metal: composite = 1:1)
[0076] A lithium secondary battery structure was manufactured in the same manner as in Example 1, except that the 12 cells A and 12 cells B produced in Example 1 were arranged in the order of ABAB ... ABAB. At this time, the ratio of the number of metal current collectors: composite conductive current collectors was set to 1:1.
[0077] Example 4: Secondary battery structure using a composite conductive current collector (metal: composite = 3:1)
[0078] The lithium secondary battery structure was manufactured in the same manner as in Example 1, except that the 18 cells A and 6 cells B produced in Example 1 were arranged in the order of AAABAAAB ... AAABAAAB. At this time, the ratio of the number of metal current collectors: composite conductive current collectors was set to 3:1.
[0079] Example 5: Secondary battery structure using a composite conductive current collector (metal: composite = 5:1)
[0080] The lithium secondary battery structure was manufactured in the same manner as in Example 1, except that the 20 cells A and 4 cells B produced in Example 1 were arranged in the order of AAAAABAAAAAB ... AAAAABAAAAAB. At this time, the ratio of the number of metal current collectors: composite conductive current collectors was set to 5:1.
[0081] Test Example 1: Performance evaluation based on the quantitative ratio of metal current collector and composite conductive current collector
[0082] The following tests were conducted to evaluate the performance of the lithium secondary battery structures of the examples and comparative examples.
[0083] 1) Measurement of initial resistance
[0084] The AC impedance value of the fabricated lithium secondary battery structure was measured at a frequency of 10 kHz, and the results are shown in Table 1 below.
[0085] 2) Evaluation of cycle life performance
[0086] The lithium secondary battery structure of the embodiment and the comparative example was initially charged and discharged (once) at room temperature. At this time, it was charged to SOC50 at a constant current (CC) of 1C rate, and then charged to SOC100 at a constant current-constant voltage (CC-CV) of 0.7C rate, and discharged to 3.0V at a rate of 0.7C. The capacity retention rate (%) was measured when a total of 300 charge / discharge cycles were performed. At this time, the capacity retention rate was calculated using the following formula 1, and the results are shown together in the following Table 1:
[0087] [Formula 1]
[0088] Capacity retention rate (%) = (discharge capacity after 300 charge-discharge cycles / discharge capacity after 1 charge-discharge cycle) × 100
[0089] 3) Stability test
[0090] A cylindrical rod with a diameter of 15.8 pie-shaped was placed on the lithium secondary battery structure of the embodiment and the comparative example, and a weight of 9.1kg was freely dropped from a height of 610mm to impact the battery, and an impact test was performed. If the battery meets the NF (no fire) and NE (no explosion) conditions, it is judged to pass. The number of passes is measured based on the total number of tests, and the pass rate (%) is evaluated thereby. The evaluation results are shown in Table 1 below.
[0091] [Table 1]
[0092]
[0093] Referring to Table 1, it was confirmed that the lithium secondary battery structures of Examples 1 to 5 had low initial resistance values and exhibited high capacity retention and excellent life characteristics even after 300 charge and discharge cycles. In particular, it was confirmed that Examples 2 to 4, in which the ratio of the metal current collector: composite conductive current collector was 1:3 to 3:1, exhibited more excellent performance.
[0094] In contrast, the lithium secondary battery structure using the single metal current collector of Comparative Example 1 exhibited poor performance in terms of stability characteristics, while the lithium secondary battery structure using the composite conductive current collector of Comparative Example 2 exhibited poor performance in terms of initial resistance value and life characteristics.
[0095] Test Example 2: Performance evaluation based on the thickness ratio of the composite conductive current collector
[0096] First, the positive electrode active material (LCO): conductive material (carbon black): binder (PVdF) was mixed in an N-methylpyrrolidone (NMP) solvent at a mass ratio of 97:1.2:1.8 to prepare a positive electrode slurry. The slurry was then coated on a composite conductive current collector having a polymer substrate (PET) and a metal layer (aluminum) with different thickness ratios at a predetermined loading amount, as shown in Table 2 below, dried, and then rolled to produce a double-sided positive electrode.
[0097] Then, as a negative electrode, the negative electrode active material (graphite): conductive material (carbon black): binder (SBR): CMC was mixed in a mass ratio of 95.35:0.5:3:1.15 to prepare a negative electrode slurry. The slurry was then applied to a current collector of 8um copper foil at a predetermined loading amount, dried, and then rolled to produce a negative electrode.
[0098] A 10 um thick separator coated with SRS on a polyolefin fabric was used as a separator between the negative electrode and the positive electrode to prepare single cell samples of Examples 6 to 7 and Comparative Examples 3 to 5. The following tests were performed to evaluate the performance of the prepared samples.
[0099] 1) Evaluation of processing performance
[0100] The single cell sample prepared above was wound on a circular column with a diameter of 80 mm to measure whether a short circuit (or crack) occurred on the electrode surface. The results are shown in Table 2 below.
[0101] 2) Evaluation of 2C output
[0102] The samples of Examples 6 to 7 and Comparative Examples 3 to 5 prepared with composite conductive current collectors having different thickness ratios of polymer substrate (PET) and metal layer (aluminum) were discharged once under 2C rate current conditions, and then 0.1C discharge capacity and capacity ratio were calculated. The results are shown in Table 2 below.
[0103] 3) Nail prick test
[0104] In the same manner as the PV8450 certification conditions, when a metal body with a diameter of 3 mm dropped at a speed of 80 mm / sec and penetrated the battery, the samples of Examples 6 to 7 and Comparative Examples 3 to 5 prepared above were evaluated for ignition. The number of times the ignition occurred was measured based on the total number of tests, and the ignition rate (%) was evaluated accordingly. The results of this evaluation are shown in Table 2 below.
[0105] [Table 2]
[0106]
[0107] Referring to Table 2, it was confirmed that Examples 6 and 7, in which the ratio of the total thickness of the polymer substrate: the total thickness of the metal layer was in the range of 1:2 to 5:1, exhibited excellent processing performance, output characteristics, and stability. In contrast, it was found that in the case of Comparative Example 3, in which the thickness ratio of the PET polymer substrate was high, not only disconnection occurred, but also the battery performance was deteriorated due to high resistance. On the other hand, it was confirmed that in the case of Comparative Example 4, in which the thickness ratio of the aluminum metal layer was high, the output characteristics were excellent, but there was no significant difference in stability from Comparative Example 5 consisting only of an aluminum metal layer.
[0108] [Explanation of Reference Numerals]
[0109] 100: first electrode, positive electrode
[0110] 100': first electrode using a composite conductive current collector, positive electrode using a composite conductive current collector
[0111] 11 0: First conductive current collector, positive electrode conductive current collector
[0112] 11 0': Composite conductive current collector
[0113] 111: Polymer substrate
[0114] 112: Metal layer
[0115] 120: Positive electrode active material layer
[0116] 200: Second electrode, negative electrode
[0117] 210: Second conductive current collector, negative electrode conductive current collector
[0118] 220: Negative electrode active material layer
[0119] 300: Partition
Claims
1. A lithium secondary battery structure, comprising a plurality of battery cells, each battery cell comprising: a first electrode comprising a first conductive current collector having an active material layer formed on at least one surface; a second electrode including a second conductive current collector having an active material layer formed on at least one surface; and a separator formed between active material layers of the first electrode and the second electrode facing each other, wherein for each battery cell, the first conductive current collector or the second conductive current collector is a metal current collector, or a composite conductive current collector having a metal layer formed on a polymer substrate, and The metal current collector:the composite conductive current collector are included in the overall battery structure in a quantitative ratio of 5:1 to 1:
5. 2 . The lithium secondary battery structure according to claim 1 , wherein the metal current collector:the composite conductive current collector are included in the overall battery structure in a quantitative ratio of 3:1 to 1:
3.
3. The lithium secondary battery structure according to claim 1, wherein the first electrode is a positive electrode, and For each battery cell, the first conductive current collector is the metal current collector or the composite conductive current collector.
4. The lithium secondary battery structure according to claim 1, wherein for each battery cell, the first conductive current collector is the metal current collector or the composite conductive current collector, and The metal current collectors and the composite conductive current collectors are regularly and alternately arranged according to a stacking sequence of the first electrodes.
5. The lithium secondary battery structure according to claim 4, wherein the metal current collector and the composite conductive current collector are configured so that, according to the stacking order of the first electrode, one composite conductive current collector is repeatedly arranged for every 1 to 3 metal current collectors, or one metal current collector is repeatedly arranged for every 1 to 3 composite conductive current collectors. 6 . The lithium secondary battery structure according to claim 1 , wherein in the composite conductive current collector, a ratio of the total thickness of the polymer substrate: the total thickness of the metal layer is 1:2 to 5:
1. 7 . The lithium secondary battery structure according to claim 3 , wherein the polymer substrate is a polyester-based resin substrate, and the metal layer is an aluminum layer.
8. The lithium secondary battery structure according to claim 7, wherein the polyester-based resin comprises at least one resin selected from the group consisting of polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN). 9 . The lithium secondary battery structure of claim 1 , wherein the first conductive current collector has a thickness ranging from 6 um to 20 um.
10. The lithium secondary battery structure according to claim 1, wherein the active material layer is formed on both surfaces of the first conductive current collector and the second conductive current collector, and The first electrodes and the second electrodes are alternately stacked with separators interposed therebetween.